Energy Efficiency Optimization for Massive MIMO Enabled UAV Communications - Ma, Xiaohan; Na, Zhenyu (International Conference on Dependable Systems and Their Applications (Online), 2022)
Benefiting from good mobility, unmanned aerial vehicles (UAVs) can reconstruct wireless connections for affected areas. Most of the existing work has usually ignored the influence of limited airborne energy on the dependability of UAV data transmission. Accordingly, this paper proposes a UAV-assisted wireless powered system to achieve dependable data collections in Internet of things (IoT). Specifically, a UAV leverages energy beamforming to transfer energy to ground users (GUs) in downlink sub-timeslot, while the GUs transmit data to the UAV with the harvested energy in uplink sub-timeslot. For this system, a joint optimization problem of sub-timeslot allocation and UAV route planning is investigated to maximize the system energy efficiency subject to UAV dynamics, time slot duration and GUs' rate threshold. To tackle the non-convexity of the formulated problem, a low-complexity alternating iterative algorithm is proposed. The simulation results demonstrate that the proposed algorithm can not only optimize UAV route, but also achieve a good compromise between system throughput and UAV propulsion energy consumption.